The Effect of Mychorrizha Enriched Seed Encapsulation to Soybean Growth and Yield - Jonet Kurniawan; Taryono Taryono (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2019)
The high number of soybean's import has led to various eﬀorts to increase soybean production through increasing productivity, expanding planting areas, and improving management. One that can be done in maximizing soybean performance is the application of biological fertilizer such as mycorrhiza because it was able to increase nutrien tuptake and water and even drought tolerance. This study aims to determine the eﬀect of encapsulation of soybean seeds enriched with mycorrhiza and explain the eﬀect of mycorrhiza on soybean growth and yield. This study used three soybean varieties namely Anjasmoro, Grobogan, and Argomulyo which treated with encapsulation + mycorrhiza, mycorrhiza addition, and without mycorrhiza. The observation include number of pods per plant, number of seeds per plant, percentage of ﬁlled pods per plant, seed weight per plant and weight of 100 seeds. Data on seed weight per plant showed signiﬁcantly diﬀerent among varieties and Anjasmoro was the highest. The application of mycorrhiza through seed encapsulation did not improve the soybean performance.